2019
DOI: 10.1007/s40037-019-00557-0
|View full text |Cite
|
Sign up to set email alerts
|

Student participation in undergraduate medical education: a continuous collective endeavour

Abstract: None

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…In a broader context, apart from academics and medical professionals, other stakeholders should also be involved as agents of this change in medical education, such as healthcare organizations and medical students [ 3 , 46 , 47 ]. However, finding the balance between learners’ personal preferences and an adherence to academic requirements and standards is a challenge that might generate frustration for some medical students.…”
Section: Discussionmentioning
confidence: 99%
“…In a broader context, apart from academics and medical professionals, other stakeholders should also be involved as agents of this change in medical education, such as healthcare organizations and medical students [ 3 , 46 , 47 ]. However, finding the balance between learners’ personal preferences and an adherence to academic requirements and standards is a challenge that might generate frustration for some medical students.…”
Section: Discussionmentioning
confidence: 99%
“…The key benefits of active student participation that were considered in a recent commentary are enhanced student satisfaction, meta-cognitive understanding of learning and teaching processes, enhanced student-staff relationships, and development of personal, professional, and academic competences of students [ 2 ]. Our results showed that particularly the development of various competences was part of the experiences of the organizing students, in addition to enhanced student-staff relationships and student satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Students are increasingly involved in designing medical curricula [ 1 , 2 ]. This article discusses the learning experiences of students who organized a large-scale teaching week for first, second and third year (bachelor phase) (bio) medical students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Santiago, Chile. paaraya2@uc.cl E l rol de los estudiantes de medicina como agentes activos en su formación ha tomado mayor relevancia en la última década 1 . Para los desafíos que enfrentarán los futuros profesionales de salud, la educación médica ha hecho esfuerzos en migrar desde un modelo informativo hacia uno que busca desarrollar habilidades de liderazgo y gestión, con el propósito de formar agentes de cambio con altas capacidades técnicas 2,3 La participación estudiantil activa implica que los estudiantes de medicina se involucran tanto en actividades de diseño, implementación, evaluación y cogobernanza curricular, como de representación y desarrollo de vida universitaria 4,5 .…”
unclassified